Musculoskeletal Problems Induced by the Cycling Activity - Paramita Dyah Lasmana (Journal of Global Pharma Technology, 2019)
ABSTRACTINTRODUCTIONThere are some musculoskeletal problems that may arise due to cycling. It may be related from overuse due to unproper bike settings. The aim of this study is to understand cycling related musculoskeletal problems.MATERIALS AND METHODSThis was an observational study conducted on 32 adult respondents who ride a bicycle at least once a week. The parameters used in this study was illeotibialband syndrome, patellar mallalignment sign, inseam frame size ratio and x ray-based measurement (insalsavati index and sulcus angle). Cross tabs and independent test were used to analyze the correlation of unusculoskeletal problems with the factors that may affect.RESULTSThere was 32 respondents with 30 readable knee x-ray. Cycling frequency and distance, apprehension test result, knee Q angle, Sulcus angle, and Insalsavati index were found to have no correlation with the occurrence of knee pain. Age, knee angle, and frame size-inseam ratio were found to have unrelation significantly with p value,0,06; 0,025,and 0,00, respectively.CONCLUSIONThis study showed that knee pain in cycling was correlated significantly with age, knee angle, and frame size-inseam ratio. These results may be used to define the best frame size of bike no prevent cycling-related musculoskeletal problems. KEYWORDSCycling; musculoskeletal problems